Pohjoisen varhaiskasvatuksen puolesta:Oulun lastentarhanopettajakoulutus vuosina 1967–1995 - Lujala, E. (Elise) (Oulun yliopisto, 2018)
Abstract This work discusses the stages of the northernmost kindergarten teacher education scheme in Finland from its foundation to the move to the university. The plans for training in Oulu started as part of an idea for a multidisciplinary teacher college, under which the training of kindergarten teachers maintained by a supporters’ association was launched in 1967. All the kindergarten teacher seminars in Finland were changed into state-run kindergarten teacher colleges in 1977. Like the temporary programs to train kindergarten teachers in the universities, they were made permanent in 1995 as programs subject to the universities’ faculties of education. A kindergarten teacher training program was established in Oulu to improve the educational circumstances and to remove the shortage of kindergarten teachers in northern Finland. Issues distinctive of Oulu were the introduction of training for men, efforts to introduce university-level study modules in education, and development of teaching methods. It was linked to increasingly advanced integration and projects between the various teaching areas and diverse child group activities. Development was significantly fostered by the completion of the building project designed for the program in 1987. The new look of the renovated premises at the seashore also added to coverage and awareness of the existence of the program. A new northern Finnish viewpoint on the training was brought by a decision on student admission in the 1980’s, according to which Sami-speaking applicants had a special pre-selection quota, and through their admission teaching expanded to the Sami areas. International activities began to develop strongly in the early 1990’s, when student and teacher exchange and cooperation started on a regular basis through the Nordplus, Erasmus and ATEE programs in addition to bilateral exchange agreements. With the increase in university-level courses, the Faculty of Education called for increased resourcing by the college for teaching them. As a result, the ...